Environment friendly synthesis of reduced graphene oxide from spent lithium-ion battery graphite and its nanocomposite with MoO3 nanorods for photocatalytic hydrogen evolution - Kangutkar, Raju S.; Walko, Priyanka; Athira, K.; Manjanna, J.; Devi, R. Nandini (Energy & Fuels, 2024)
Photocatalytic water splitting from solar H2 generation systems is of great interest as a sustainable fuel and an environmentally benign approach. A photocatalyst should be cost-efficient and highly productive to obtain a green H2 fuel. Thus, photocatalytic water splitting is significant for real-world applications. In the present work, we have successfully synthesized MoO3@rGO nanocomposite material with heterojunction as a stable and high-performance photocatalyst for the H2 evolution reaction in deionized (DI) water and natural seawater. First, MoO3 was prepared through a low-temperature hydrothermal method and composites with graphene oxide (GO) and reduced graphene oxide (rGO) precursors, followed by ultrasonication. rGO was obtained from GO, which is obtained from the spent graphite (anode material) by the modified Hummer's method. The rGO powder was reduced by an ascorbic acid-reducing agent under microwave irradiation using GO. The nanocomposite materials were characterized using XRD, Raman spectra, XPS, photoluminescence, FE-SEM, HR-TEM, and BET. The photocatalytic water splitting ability of MoO3@rGO was measured under visible light (lambda >= 420 nm) irradiation with the TEOA sacrificial reagent. The H2 generation rate in DI water and natural seawater was found to be 2183.41 and 2294.26 mu mol g-1 h-1, with an apparent quantum efficiency (AQE) of 5.72 and 5.98%, respectively. Such a high rate of H2 generated is ascribed to the novel surface contact between MoO3 and the rGO sheet as evident from HR-TEM images, wherein the rGO sheet is seen wrapped around MoO3. Consequently, the synergistic effect between MoO3 and rGO sheets is expected without the use of any other cocatalysts. Thus, electron-hole recombination is significantly minimized during the water reduction reaction. We believe that the MoO3@rGO nanocomposite is a potential photocatalyst for energy production.

Photocatalytic hydrogen evolution by MoO3@g-C3N4 and MoO3@f-MWCNT nanocomposites in deionized and natural seawater under visible light - Kangutkar, Raju S.; Walko, Priyanka; Dhepe, P. L.; Nayaka, G. P.; Manjanna, J. (ACS Applied Nano Materials, 2025)
Visible-light-driven photocatalysts are predominantly useful for converting solar to hydrogen energy via photocatalytic water-splitting reactions. The heterojunction composite materials have exhibited remarkable advantages for visible-light photocatalytic H-2 evolution. We have successfully synthesized MoO3@f-MWCNT and MoO3@g-C3N4 nanocomposites and characterized them using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water-splitting efficiency of MoO3@f-MWCNT and MoO3@g-C3N4 was measured under visible light (lambda >= 420 nm) irradiation using TEOA as a sacrificial reagent in DI water and natural seawater. The H-2 evolution rate in DI water for MoO3@f-MWCNT is 2313.56 mu mol g(-)(1) h(-)(1), and for MoO3@g-C3N4 is 2530.35 mu mol g(-1) h(-1) with an apparent quantum efficiency (AQE) of 6.38 and 6.93%, respectively. In natural seawater, the H-2 evolution rate is 2632.20 and 2845.06 mu mol g(-1) h(-1), with an AQE of 7.21 and 7.77%, respectively. The rate of H-2 evolution slightly increased in natural seawater than DI water. The Tafel slope values for MoO3@g-C3N4 and MoO3@f-MWCNT are 59 and 92 mV dec(-1), respectively. The lowest Tafel value of MoO3@g-C3N4 exhibited a faster rate of reaction. Thus, the surface interaction between the MoO3 and the porous g-C3N4 materials may create synergistic effects, which facilitate electron transport at the interface and significantly boost the photocatalytic activity. Thus, MoO3@g-C3N4 is a promising photocatalyst for renewable energy production.
Keywords: deionized water; electrochemicalHER; MoO3@f-MWCNT; MoO3@g-C3N4 nanocomposites; natural seawater; photocatalytic H-2 evolution

Enhanced photocatalytic hydrogen evolution in deionized/natural seawater and removal of organic pollutants using the heterostructure of CuO/Cu2O nanoparticles under visible light - Kangutkar, Raju S.; Walko, Priyanka; Nayaka, Girish Praveen; Nigam, Sandeep; Majumder, Chiranjib; Manjanna, Jayappa (Langmuir, 2026)
Water splitting for hydrogen production and reducing water pollution using solar light are part of the Sustainable Development Goals, which require highly active photocatalytic materials. The heterostructures have demonstrated remarkable photocatalytic advantages in visible light. Herein, we report microwave-assisted green synthesis of CuO/Cu2O nanoparticles using Tridax plant leaf extract. The synthesized nanoparticles were characterized by using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water splitting performance of CuO/Cu2O and CuO was measured under visible light (lambda >= 420 nm) irradiation using methanol as a sacrificial reagent in DI water and natural seawater. The H2 evolution rates in DI water for CuO/Cu2O and CuO are 2043.21 and 970.09 mu mol g-1 h-1 with apparent quantum efficiency (AQE) values of 5.60 and 2.66 %, respectively. In natural seawater, the H2 evolution rates are 2599.29 and 1370.54 mu mol g-1 h-1 with AQE values of 7.12 and 3.75 %, respectively. The rate of H2 evolution slightly increased in natural seawater. Also, the degradation of the methylene blue dye was examined here, and the efficiency of CuO/Cu2O was determined to be 97 % under natural sunlight. Electrocatalytic H2 evolution was also studied here by using linear sweep voltammetry. Tafel slope values for CuO/Cu2O and CuO are 153 and 250 mV dec-1, respectively. The lowest Tafel value of CuO/Cu2O indicates a faster rate of reaction, thereby producing easier charge separation and lowering the electron-hole recombination due to the presence of surface defects, smaller particle size, enhanced crystallinity, and the synergistic effect between Cu2O and CuO.